Plant-based antibacterial deodorizing fiber and preparation method thereof

By combining low-temperature plasma treatment with modified nanomaterials, plant-based antibacterial and deodorizing fibers were prepared, solving the problems of low antibacterial performance, poor flame retardancy, and easy aging of polylactic acid fibers, and achieving multi-functional improvement.

CN120945662APending Publication Date: 2025-11-14NANTONG DEKA TEXTILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511273771.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing polylactic acid fibers have low antibacterial properties, poor flame retardancy, and are prone to aging, making it difficult to meet the diverse needs of high-end textiles.

Method used

Ammoniated fibers were prepared by low-temperature plasma treatment, and modified nano-titanium dioxide and modified nano-cellulose were mixed with polylactic acid and melt-spun. Combined with phenylphosphonic acid treatment, antibacterial, flame retardant and anti-ultraviolet functions were introduced.

Benefits of technology

This technology enhances the antibacterial, deodorizing, flame-retardant, and UV-resistant properties of polylactic acid fibers, extending their service life and meeting the requirements of high-end textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005585457100000101
    Figure BDA0005585457100000101
  • Figure BDA0005585457100000111
    Figure BDA0005585457100000111
Patent Text Reader

Abstract

The invention discloses a plant-based antibacterial and deodorant fiber and a preparation method thereof, and relates to the field of fibers. When the plant-based antibacterial and deodorant fiber is prepared, titanium dioxide is pre-modified by using gamma-glycidyl ether oxypropyl trimethoxy silane, and then is grafted with 3-amino-5-methyl-4H-1, 2, 4 triazole, so that modified nano titanium dioxide is prepared; the preparation method comprises the following steps: sulfonating nano-cellulose, and reacting with hexadecyl trimethyl ammonium bromide to prepare modified nano-cellulose; carrying out melt spinning on the modified nano titanium dioxide, the modified nano cellulose and polylactic acid to prepare polylactic acid fibers; carrying out low-temperature plasma treatment on the polylactic acid fibers to prepare ammoniated fibers; and immersing the ammoniated fiber in a post-treatment solution prepared from phenylphosphonic acid, ethanol and deionized water to prepare the plant-based antibacterial and deodorant fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fibers, specifically to a plant-based antibacterial and deodorizing fiber and its preparation method. Background Technology

[0002] Polylactic acid (PLA) is a renewable bio-based polymer material with broad application prospects in textiles, packaging, and medical fields due to its excellent biodegradability, biocompatibility, and processing properties. However, existing PLA fibers suffer from problems such as low antibacterial properties, poor flame retardancy, and easy aging, which limit their application in high-performance textiles and functional fibers.

[0003] Polylactic acid (PLA) is polymerized from lactic acid monomers, and its molecular chain contains almost no active functional groups that can kill or inhibit microorganisms. The fiber surface lacks positive charges or the ability to release active substances, thus offering little inhibitory effect on the attachment and reproduction of bacteria and fungi. Especially in humid or warm environments, microorganisms easily proliferate on the fiber surface, leading not only to odors but also potentially causing mold growth, performance degradation, and even harm to the user's health.

[0004] Polylactic acid (PLA) is an aliphatic polyester with a chemical structure primarily composed of carbon-hydrogen bonds, carbon-oxygen double bonds, and carbon-oxygen bonds. It has relatively low thermal stability, decomposing into flammable small molecules during combustion and failing to form a dense carbon layer, resulting in limited flame-retardant properties. Under the influence of an ignition source, PLA fibers are prone to rapid melting and dripping, posing a safety hazard. This is particularly true in applications such as home textiles, automotive interiors, and fabrics used in public places, where higher flame-retardant requirements are necessary.

[0005] Polylactic acid (PLA) molecules contain ester bonds, making them susceptible to photodegradation induced by ultraviolet (UV) light. UV light damages the molecular chains, leading to chain breakage, yellowing, and reduced mechanical properties. Prolonged exposure to sunlight or UV lamps causes PLA fibers to age quickly and have a shortened lifespan. This is a limiting factor for their widespread adoption in fields requiring high photostability, such as outdoor sportswear and protective materials.

[0006] While polylactic acid (PLA) fiber is environmentally friendly, it lacks antibacterial, flame-retardant, and UV-resistant properties, making it difficult to meet the increasingly diverse demands of high-end textiles. How to endow PLA fiber with multiple functions (antibacterial, deodorizing, flame-retardant, and UV-resistant) through green, safe, and sustainable methods has become a research hotspot and technical challenge in this field. Summary of the Invention

[0007] The purpose of this invention is to provide a plant-based antibacterial and deodorizing fiber and its preparation method, so as to solve the problems existing in the prior art.

[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0009] A plant-based antibacterial and deodorizing fiber, wherein the plant-based antibacterial and deodorizing fiber is obtained by treating ammoniated fiber with a post-treatment solution.

[0010] As an optimization, the ammoniated fiber is obtained by low-temperature plasma treatment of polylactic acid fiber.

[0011] As an optimization, the polylactic acid fiber is obtained by melt spinning polylactic acid, modified nano-titanium dioxide, and modified nano-cellulose.

[0012] As an optimization, the modified nano-titanium dioxide is prepared by pre-modifying γ-glycidoxypropyltrimethoxysilane and then grafting it with 3-amino-5-methyl-4H-1,2,4-triazole.

[0013] As an optimization, the modified nanocellulose is prepared by reacting nanocellulose with hexadecyltrimethylammonium bromide after sulfonation.

[0014] As an optimization, the post-treatment solution is prepared from phenylphosphonic acid, ethanol and deionized water.

[0015] A method for preparing plant-based antibacterial and deodorizing fibers includes the following preparation steps:

[0016] (1) Mix nano-titanium dioxide, ethanol, and deionized water in a mass ratio of 1:(18-20):(1-2), disperse ultrasonically, adjust the pH to 4.5-5.5 with glacial acetic acid, add 5-7 times the mass of nano-titanium dioxide, stir at 800 r / min for 2-3 h at room temperature, raise the temperature to 60℃, continue stirring and reflux for 0.5-1.5 h, filter, wash 3 times with anhydrous ethanol, and dry at 50-60℃ under vacuum for 10-15 h. Pre-modified nano-titanium dioxide was prepared by mixing pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol in a mass ratio of 1:(3~4):(0.02~0.04):(19~21). The mixture was stirred at 80~90℃ and 400~500r / min for 4~6h. The mixture was filtered, washed three times with anhydrous ethanol, and dried at 50~60℃ under vacuum for 10~12h to obtain modified nano-titanium dioxide.

[0017] (2) A sulfonated nanocellulose suspension was prepared by mixing nanocellulose with a mass ratio of 1:(30-34) and 64%wt sulfuric acid aqueous solution, stirring at 400-500 r / min for 30-50 min at 40-50℃, and dialysis with ultrapure water. The sulfonated nanocellulose suspension was then mixed with a 4.4 mM hexadecyltrimethylammonium bromide aqueous solution at a mass ratio of 1:(97-99), and the pH was adjusted to 10 with 1 mol / L sodium hydroxide aqueous solution. The mixture was stirred at 400-500 r / min for 2-4 h at 55-65℃, cooled naturally to room temperature, and stirred for another 12 h. The mixture was then centrifuged, washed three times with deionized water, and dried at 50-60℃ for 10-12 h under vacuum to obtain modified nanocellulose.

[0018] (3) Polylactic acid, modified nano-titanium dioxide and modified nano-cellulose in a mass ratio of (18-20):1:1 are added to a melt spinning machine for melt spinning. After spinning, the fibers are immersed in deionized water for cooling and placed in a hot stretching box. The temperature is set to 60-80℃, the stretching ratio is 3.5 times, and the winding speed is 1000m / min to obtain polylactic acid fiber.

[0019] (4) Polylactic acid fiber is subjected to plasma treatment using a low-temperature plasma treatment instrument. The temperature is set to 20°C, the vacuum is drawn to 35Pa, the pressure reducing valve is opened, ammonia is introduced, and low-temperature plasma treatment is performed to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water are mixed evenly in a mass ratio of 1:(1~2):(19~20) to prepare a post-treatment solution. The ammoniated fiber is immersed in the post-treatment solution and reacted at 60~70°C for 10~12h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0020] As an optimization, the melt spinning parameters in step (3) are: melt temperature of 170-185℃ and spinneret diameter of 0.25-0.35mm.

[0021] As an optimization, the model of the low-temperature plasma processor is DT-03.

[0022] As an optimization, the low-temperature plasma treatment parameters in step (4) are: power (198~202)w, time (178~182)s.

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] In preparing plant-based antibacterial and deodorizing fibers, this invention involves crosslinking titanium dioxide with γ-glycidoxypropyltrimethoxysilane to introduce epoxy groups, thus obtaining pre-modified nano-titanium dioxide. Then, the epoxy groups of the pre-modified nano-titanium dioxide react with the amino group of 3-amino-5-methyl-4H-1,2,4-triazole to introduce an antibacterial agent, resulting in modified nano-titanium dioxide. Nanocellulose is hydrolyzed and sulfonated with sulfuric acid to obtain a sulfonated nanocellulose suspension. The sulfonic acid groups of the particles in the sulfonated nanocellulose suspension are positively and negatively charged with hexadecyltrimethylammonium bromide, introducing a quaternary ammonium structure, thus obtaining modified nanocellulose. The modified nano-titanium dioxide, modified nanocellulose, and polylactic acid are mixed and melt-spun to obtain polylactic acid fibers. The polylactic acid fibers are then subjected to isothermal plasma treatment to obtain ammoniated fibers. Finally, the ammoniated fibers are immersed in a post-treatment solution prepared from phenylphosphonic acid, ethanol, and deionized water to obtain plant-based antibacterial and deodorizing fibers.

[0025] First, the raw materials used in the preparation contain polylactic acid and nanocellulose, which are plant-based materials with good degradation effects. Pre-modified nano-titanium dioxide is prepared by reacting titanium dioxide with γ-glycidoxypropyltrimethoxysilane. Modified nano-titanium dioxide is then prepared by grafting the pre-modified nano-titanium dioxide with 3-amino-5-methyl-4H-1,2,4-triazole. Titanium dioxide can absorb ultraviolet light and simultaneously utilize the energy of ultraviolet light to generate free radicals, damaging cells and giving the fiber anti-ultraviolet and antibacterial effects. 3-amino-5-methyl-4H-1,2,4-triazole can destroy bacterial cell membranes and inhibit bacterial enzyme activity, thus achieving an antibacterial effect.

[0026] Secondly, sulfonated nanocellulose is prepared to obtain a sulfonated nanocellulose suspension, which is then reacted with hexadecyltrimethylammonium bromide to obtain modified nanocellulose. Modified nanocellulose is then produced by melt spinning a mixture of modified nano-titanium dioxide, modified nanocellulose, and polylactic acid to obtain polylactic acid fiber. After sulfonation, the nanocellulose becomes negatively charged under alkaline conditions, creating the possibility of electrostatic adsorption. Through electrostatic adsorption of hexadecyltrimethylammonium bromide, the quaternary ammonium will increase the broad-spectrum antibacterial activity of the fiber by disrupting the structure of biological cell membranes.

[0027] Finally, polylactic acid fibers were treated with isothermal plasma to introduce amino groups onto the surface, resulting in ammoniated fibers. These ammoniated fibers were then reacted with phenylphosphonic acid to introduce flame-retardant groups, producing plant-based antibacterial and deodorizing fibers. Low-temperature plasma treatment introduced amino groups onto the fiber surface, facilitating subsequent modification. The ammoniated fibers reacted with phenylphosphonic acid; during combustion, phenylphosphonic acid formed a dense char layer on the surface, isolating oxygen and reducing heat transfer, thus achieving a flame-retardant effect. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] To more clearly illustrate the method provided by the present invention, the following embodiments will be described in detail.

[0030] Example 1

[0031] A method for preparing plant-based antibacterial and deodorizing fibers mainly includes the following steps:

[0032] (1) Nano-titanium dioxide, ethanol and deionized water were mixed in a mass ratio of 1:18:1, ultrasonically dispersed, and the pH was adjusted to 4.5 with glacial acetic acid. γ-glycidyl etheroxypropyltrimethoxysilane was added in 5 times the mass of nano-titanium dioxide. The mixture was stirred at 800 r / min for 2 h at room temperature, heated to 60 °C, and stirred and refluxed for 0.5 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 50 °C for 10 h under vacuum to obtain pre-modified nano-titanium dioxide. Pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol were mixed evenly in a mass ratio of 1:3:0.02:19 and stirred at 400 r / min for 4 h at 80 °C. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 50 °C for 10 h under vacuum to obtain modified nano-titanium dioxide.

[0033] (2) Nanocellulose with a mass ratio of 1:30 and 64%wt sulfuric acid aqueous solution were mixed and stirred at 400r / min for 30min at 40℃. After dialysis with ultrapure water, sulfonated nanocellulose suspension was obtained. The sulfonated nanocellulose suspension with a mass ratio of 1:97 and 4.4mM hexadecyltrimethylammonium bromide aqueous solution were mixed and the pH was adjusted to 10 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 400r / min for 2h at 55℃, cooled naturally to room temperature, stirred for 12h, separated by centrifugation, washed 3 times with deionized water, and dried at 50℃ for 10h under vacuum to obtain modified nanocellulose.

[0034] (3) Polylactic acid, modified nano-titanium dioxide and modified nano-cellulose in a mass ratio of 18:1:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 170℃, the spinneret diameter was 0.25mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 60℃, a stretching ratio of 3.5 times and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0035] (4) Polylactic acid fiber was subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum was evacuated to 35 Pa, the pressure reducing valve was opened, ammonia was introduced, the power was set to 198 W, and the treatment was carried out for 178 s to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water were mixed evenly in a mass ratio of 1:1:19 to prepare a post-treatment solution. The ammoniated fiber was immersed in the post-treatment solution and reacted at 60 °C for 10 h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0036] Example 2

[0037] A method for preparing plant-based antibacterial and deodorizing fibers mainly includes the following steps:

[0038] (1) Nano-titanium dioxide, ethanol and deionized water were mixed in a mass ratio of 1:19:1.5, ultrasonically dispersed, and the pH was adjusted to 5 with glacial acetic acid. γ-glycidyl etheroxypropyltrimethoxysilane was added in 6 times the mass of nano-titanium dioxide. The mixture was stirred at 800 r / min for 2.5 h at room temperature, heated to 60 °C, and stirred and refluxed for 1 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 55 °C for 11 h under vacuum to obtain pre-modified nano-titanium dioxide. Pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol were mixed evenly in a mass ratio of 1:3.5:0.03:20 and stirred at 450 r / min for 5 h at 85 °C. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 55 °C for 11 h under vacuum to obtain modified nano-titanium dioxide.

[0039] (2) Nanocellulose with a mass ratio of 1:32 and 64%wt sulfuric acid aqueous solution were mixed and stirred at 450r / min for 40min at 45℃. After dialysis with ultrapure water, sulfonated nanocellulose suspension was obtained. The sulfonated nanocellulose suspension with a mass ratio of 1:98 and 4.4mM hexadecyltrimethylammonium bromide aqueous solution were mixed and the pH was adjusted to 10 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 450r / min for 3h at 60℃. After natural cooling to room temperature, stirring was continued for 12h. The mixture was centrifuged, washed 3 times with deionized water, and dried at 55℃ for 11h under vacuum to obtain modified nanocellulose.

[0040] (3) Polylactic acid, modified nano-titanium dioxide and modified nano-cellulose in a mass ratio of 19:1:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 177.5℃, the spinneret diameter was 0.3mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 70℃, a stretching ratio of 3.5 times and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0041] (4) Polylactic acid fiber was subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum was evacuated to 35 Pa, the pressure reducing valve was opened, ammonia was introduced, the power was set to 200 W, and the treatment was carried out for 180 s to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water were mixed evenly in a mass ratio of 1:1.5:19.5 to prepare a post-treatment solution. The ammoniated fiber was immersed in the post-treatment solution and reacted at 65 °C for 11 h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0042] Example 3

[0043] A method for preparing plant-based antibacterial and deodorizing fibers mainly includes the following steps:

[0044] (1) Nano-titanium dioxide, ethanol and deionized water were mixed in a mass ratio of 1:20:2, ultrasonically dispersed, and the pH was adjusted to 5.5 with glacial acetic acid. γ-glycidyl etheroxypropyltrimethoxysilane was added in 7 times the mass of nano-titanium dioxide. The mixture was stirred at 800 r / min for 3 h at room temperature, heated to 60 °C, and stirred and refluxed for 1.5 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 60 °C for 12 h under vacuum to obtain pre-modified nano-titanium dioxide. Pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol were mixed evenly in a mass ratio of 1:4:0.04:21 and stirred at 500 r / min for 6 h at 90 °C. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 60 °C for 12 h under vacuum to obtain modified nano-titanium dioxide.

[0045] (2) A sulfonated nanocellulose suspension was prepared by mixing nanocellulose with a mass ratio of 1:34 and 64%wt sulfuric acid aqueous solution, stirring at 500r / min for 50min at 50℃, and dialysis with ultrapure water. The sulfonated nanocellulose suspension was then mixed with 4.4mM hexadecyltrimethylammonium bromide aqueous solution and the pH was adjusted to 10 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 500r / min for 4h at 65℃, cooled naturally to room temperature, and stirred for another 12h. The mixture was then centrifuged, washed three times with deionized water, and dried at 60℃ for 12h under vacuum to obtain modified nanocellulose.

[0046] (3) Polylactic acid, modified nano-titanium dioxide and modified nano-cellulose in a mass ratio of 20:1:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 185℃, the spinneret orifice diameter was 0.35mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 80℃, a stretching ratio of 3.5 times and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0047] (4) Polylactic acid fiber was subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum was evacuated to 35 Pa, the pressure reducing valve was opened, ammonia was introduced, the power was set to 202 W, and the treatment was carried out for 182 s to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water were mixed evenly in a mass ratio of 1:2:20 to prepare a post-treatment solution. The ammoniated fiber was immersed in the post-treatment solution and reacted at 70 °C for 12 h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0048] Comparative Example 1

[0049] (1) Nano-titanium dioxide, ethanol and deionized water in a mass ratio of 1:19:1.5 were mixed and ultrasonically dispersed. The pH was adjusted to 5 with glacial acetic acid. γ-glycidyl etheroxypropyltrimethoxysilane with a mass ratio of 6 times that of nano-titanium dioxide was added. The mixture was stirred at 800 r / min for 2.5 h at room temperature, heated to 60 °C, and stirred and refluxed for 1 h. The mixture was filtered, washed 3 times with anhydrous ethanol, and dried at 55 °C for 11 h under vacuum to obtain pre-modified nano-titanium dioxide.

[0050] (2) Nanocellulose with a mass ratio of 1:32 and 64%wt sulfuric acid aqueous solution were mixed and stirred at 450r / min for 40min at 45℃. After dialysis with ultrapure water, sulfonated nanocellulose suspension was obtained. The sulfonated nanocellulose suspension with a mass ratio of 1:98 and 4.4mM hexadecyltrimethylammonium bromide aqueous solution were mixed and the pH was adjusted to 10 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 450r / min for 3h at 60℃. After natural cooling to room temperature, stirring was continued for 12h. The mixture was centrifuged, washed 3 times with deionized water, and dried at 55℃ for 11h under vacuum to obtain modified nanocellulose.

[0051] (3) Polylactic acid, modified nano-titanium dioxide and pre-modified nano-cellulose in a mass ratio of 19:1:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 177.5℃, the spinneret diameter was 0.3mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 70℃, a stretching ratio of 3.5 times, and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0052] (4) Polylactic acid fiber was subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum was evacuated to 35 Pa, the pressure reducing valve was opened, ammonia was introduced, the power was set to 200 W, and the treatment was carried out for 180 s to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water were mixed evenly in a mass ratio of 1:1.5:19.5 to prepare a post-treatment solution. The ammoniated fiber was immersed in the post-treatment solution and reacted at 65 °C for 11 h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0053] Comparative Example 2

[0054] A method for preparing plant-based antibacterial and deodorizing fibers mainly includes the following steps:

[0055] (1) Nanocellulose with a mass ratio of 1:32 and 64%wt sulfuric acid aqueous solution were mixed and stirred at 450r / min for 40min at 45℃. After dialysis with ultrapure water, sulfonated nanocellulose suspension was obtained. The sulfonated nanocellulose suspension with a mass ratio of 1:98 and 4.4mM hexadecyltrimethylammonium bromide aqueous solution were mixed and the pH was adjusted to 10 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 450r / min for 3h at 60℃. After natural cooling to room temperature, stirring was continued for 12h. The mixture was centrifuged, washed 3 times with deionized water, and dried at 55℃ for 11h under vacuum to obtain modified nanocellulose.

[0056] (2) Polylactic acid and modified nanocellulose with a mass ratio of 19:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 177.5℃, the spinneret diameter was 0.3mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 70℃, a stretching ratio of 3.5 times, and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0057] (3) Polylactic acid fiber was subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum was evacuated to 35 Pa, the pressure reducing valve was opened, ammonia was introduced, the power was set to 200 W, and the treatment was carried out for 180 s to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water were mixed evenly in a mass ratio of 1:1.5:19.5 to prepare a post-treatment solution. The ammoniated fiber was immersed in the post-treatment solution and reacted at 65 °C for 11 h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0058] Comparative Example 3

[0059] A method for preparing plant-based antibacterial and deodorizing fibers mainly includes the following steps:

[0060] (1) Nano-titanium dioxide, ethanol and deionized water were mixed in a mass ratio of 1:19:1.5, ultrasonically dispersed, and the pH was adjusted to 5 with glacial acetic acid. γ-glycidyl etheroxypropyltrimethoxysilane was added in 6 times the mass of nano-titanium dioxide. The mixture was stirred at 800 r / min for 2.5 h at room temperature, heated to 60 °C, and stirred and refluxed for 1 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 55 °C for 11 h under vacuum to obtain pre-modified nano-titanium dioxide. Pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol were mixed evenly in a mass ratio of 1:3.5:0.03:20 and stirred at 450 r / min for 5 h at 85 °C. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 55 °C for 11 h under vacuum to obtain modified nano-titanium dioxide.

[0061] (3) Polylactic acid and modified nano-titanium dioxide with a mass ratio of 19:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 177.5℃, the spinneret diameter was 0.3mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 70℃, a stretching ratio of 3.5 times, and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0062] (4) Polylactic acid fiber was subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum was evacuated to 35 Pa, the pressure reducing valve was opened, ammonia was introduced, the power was set to 200 W, and the treatment was carried out for 180 s to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water were mixed evenly in a mass ratio of 1:1.5:19.5 to prepare a post-treatment solution. The ammoniated fiber was immersed in the post-treatment solution and reacted at 65 °C for 11 h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

[0063] Comparative Example 4

[0064] A method for preparing plant-based antibacterial and deodorizing fibers mainly includes the following steps:

[0065] (1) Nano-titanium dioxide, ethanol and deionized water were mixed in a mass ratio of 1:19:1.5, ultrasonically dispersed, and the pH was adjusted to 5 with glacial acetic acid. γ-glycidyl etheroxypropyltrimethoxysilane was added in 6 times the mass of nano-titanium dioxide. The mixture was stirred at 800 r / min for 2.5 h at room temperature, heated to 60 °C, and stirred and refluxed for 1 h. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 55 °C for 11 h under vacuum to obtain pre-modified nano-titanium dioxide. Pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol were mixed evenly in a mass ratio of 1:3.5:0.03:20 and stirred at 450 r / min for 5 h at 85 °C. After filtration, the mixture was washed three times with anhydrous ethanol and dried at 55 °C for 11 h under vacuum to obtain modified nano-titanium dioxide.

[0066] (2) Nanocellulose with a mass ratio of 1:32 and 64%wt sulfuric acid aqueous solution were mixed and stirred at 450r / min for 40min at 45℃. After dialysis with ultrapure water, sulfonated nanocellulose suspension was obtained. The sulfonated nanocellulose suspension with a mass ratio of 1:98 and 4.4mM hexadecyltrimethylammonium bromide aqueous solution were mixed and the pH was adjusted to 10 with 1mol / L sodium hydroxide aqueous solution. The mixture was stirred at 450r / min for 3h at 60℃. After natural cooling to room temperature, stirring was continued for 12h. The mixture was centrifuged, washed 3 times with deionized water, and dried at 55℃ for 11h under vacuum to obtain modified nanocellulose.

[0067] (3) Polylactic acid, modified nano-titanium dioxide and modified nano-cellulose in a mass ratio of 19:1:1 were added to a melt spinning machine for melt spinning. The melting temperature was set to 177.5℃, the spinneret diameter was 0.3mm, and after spinning, the fibers were immersed in deionized water for cooling. The fibers were then placed in a hot stretching box with a temperature of 70℃, a stretching ratio of 3.5 times and a winding speed of 1000m / min to obtain polylactic acid fibers.

[0068] Experimental Example 1

[0069] Antibacterial and deodorizing properties test of fibers

[0070] Test method: According to GB / T20944.3-2008 "Evaluation of antimicrobial properties of textiles - Part III: Shaking method": A bacterial suspension with a concentration of 1.0×10^5 CFU / mL was used, and a cotton fabric was taken as a blank control. At 20℃, the fibers of Example 2 and Comparative Examples 1-4 were spun into fabrics of the same size as the cotton fabric control. These fabrics were then placed in sealed containers containing the bacterial suspension and continuously shaken for 18 hours. The bacterial suspension after contact was cultured, and the inhibition rate was calculated using the following formula:

[0071] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.7 Comparative Example 1 85.7 Example 2 99.7 Comparative Example 2 72.6 Example 3 99.8 Comparative Example 3 80.5 Comparative Example 4 97.8

[0072] Compared to Examples 1-3, Comparative Example 1 lacked the step of grafting 3-amino-5-methyl-4H-1,2,4-triazole. 3-amino-5-methyl-4H-1,2,4-triazole possesses a nitrogen heterocycle, which can bind to the active site of enzymes, inhibiting cell wall synthases or nucleic acid-related enzymes, thus providing a certain antibacterial effect to the fiber. Therefore, the antibacterial performance of Comparative Example 1 is lower than that of Examples 1-3. Comparative Example 2, compared to Examples 1-3, completely removed the modified nano-titanium dioxide filler. Titanium dioxide can also generate its own energy by absorbing ultraviolet light. Because the radicals destroy cell structure, thereby achieving an antibacterial effect, the antibacterial performance of Comparative Example 2 is lower than that of Examples 1-3. Compared with Examples 1-3, Comparative Example 3 completely removed the modified nanocellulose filler. The modified nanocellulose contains hexadecyltrimethylammonium bromide. Quaternary ammonium can bind to anionic groups on proteins or enzymes, causing structural denaturation or inactivation, thereby achieving an antibacterial effect. Therefore, the antibacterial performance of Comparative Example 3 is lower than that of Examples 1-3. Comparative Example 4 is basically the same as Examples 1-3 in terms of antibacterial groups, so the antibacterial performance is similar.

[0073] Examples 1-3 have higher antibacterial properties compared to Comparative Examples 1-4. Deodorization and antibacterial properties are closely related. Most domestic or industrial odors come from the decomposition products of microorganisms. By inhibiting or killing these odor-producing microorganisms, the generation of odor molecules can be directly reduced. Therefore, Example 2 has stronger deodorization performance.

[0074] Experimental Example 2

[0075] UV resistance test of fibers

[0076] Test method: Referring to GB / T3916-2013, the breaking strength A of the examples and comparative examples was tested using a YG061F electronic single yarn tensile tester; the examples and comparative examples were irradiated with a xenon lamp for 10 days, and the breaking strength B of the examples and comparative examples after ultraviolet light treatment was tested. The rate of change of breaking strength of the examples and comparative examples before and after ultraviolet aging treatment was calculated; the rate of change of breaking strength = (AB) / A × 100%.

[0077] Rate of change of fracture strength (%) Rate of change of fracture strength (%) Example 1 1.22 Comparative Example 1 2.88 Example 2 1.17 Comparative Example 2 17.98 Example 3 1.18 Comparative Example 3 1.97 Comparative Example 4 1.28

[0078] The rate of change of breaking strength after aging of Comparative Examples 1 to 3 was compared with that of Comparative Example 2. The rate of change of breaking strength of other fibers was within 1 to 3%. Except for Comparative Example 2, the fillers of the tested fibers all contained titanium dioxide. Titanium dioxide not only has a high refractive index, but also can absorb some ultraviolet rays, thus protecting the fiber structure.

[0079] Experimental Example 3

[0080] Flame retardant performance test of fibers

[0081] Test method: According to standard GB / T5455-2014, take Example 2 and Comparative Examples 1 to 4 and weave them into 10cm*10cm fabrics. Hang them in a special test chamber and burn them with a specified propane gas flame at the center point of the lower edge of the fabric for 12s. Then remove the flame and observe and record the burning behavior of the samples.

[0082]

[0083]

[0084] Examples 1-3 and Comparative Examples 1-3 all have low afterflame time, smoldering time and damage length. The comparative examples burn out within 8 seconds. During fiber production, Examples 1-3 and Comparative Examples 1-3 all undergo surface amination and grafting of phenylphosphonic acid. When phenylphosphonic acid burns, it dehydrates to produce polyphosphoric acid. The polyphosphoric acid reacts with other components on the fiber to form a dense char layer, thereby achieving a flame-retardant effect.

[0085] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.

Claims

1. A plant-based antibacterial and deodorizing fiber, characterized in that, The plant-based antibacterial and deodorizing fiber is obtained by treating ammoniated fiber with a post-treatment solution.

2. The plant-based antibacterial and deodorizing fiber according to claim 1, characterized in that, The ammoniated fiber is obtained by low-temperature plasma treatment of polylactic acid fiber.

3. The plant-based antibacterial and deodorizing fiber according to claim 2, characterized in that, The polylactic acid fiber is obtained by melt spinning polylactic acid, modified nano-titanium dioxide, and modified nano-cellulose.

4. The plant-based antibacterial and deodorizing fiber according to claim 3, characterized in that, The modified nano-titanium dioxide was prepared by pre-modifying γ-glycidoxypropyltrimethoxysilane and then grafting it with 3-amino-5-methyl-4H-1,2,4-triazole.

5. The plant-based antibacterial and deodorizing fiber according to claim 3, characterized in that, The modified nanocellulose is prepared by reacting nanocellulose with hexadecyltrimethylammonium bromide after sulfonation.

6. The plant-based antibacterial and deodorizing fiber according to claim 1, characterized in that, The post-treatment solution was prepared from phenylphosphonic acid, ethanol and deionized water.

7. A method for preparing plant-based antibacterial and deodorizing fibers, characterized in that, The preparation steps include the following: (1) Mix nano-titanium dioxide, ethanol, and deionized water in a mass ratio of 1:(18-20):(1-2), disperse ultrasonically, adjust the pH to 4.5-5.5 with glacial acetic acid, add 5-7 times the mass of nano-titanium dioxide, stir at 800 r / min for 2-3 h at room temperature, raise the temperature to 60℃, continue stirring and reflux for 0.5-1.5 h, filter, wash 3 times with anhydrous ethanol, and dry at 50-60℃ under vacuum for 10-15 h. Pre-modified nano-titanium dioxide was prepared by mixing pre-modified nano-titanium dioxide, 3-amino-5-methyl-4H-1,2,4-triazole, trifluoroacetic acid and anhydrous ethanol in a mass ratio of 1:(3~4):(0.02~0.04):(19~21). The mixture was stirred at 80~90℃ and 400~500r / min for 4~6h. The mixture was filtered, washed three times with anhydrous ethanol, and dried at 50~60℃ under vacuum for 10~12h to obtain modified nano-titanium dioxide. (2) A sulfonated nanocellulose suspension was prepared by mixing nanocellulose with a mass ratio of 1:(30-34) and 64%wt sulfuric acid aqueous solution, stirring at 400-500 r / min for 30-50 min at 40-50℃, and dialysis with ultrapure water. The sulfonated nanocellulose suspension was then mixed with a 4.4 mM hexadecyltrimethylammonium bromide aqueous solution at a mass ratio of 1:(97-99), and the pH was adjusted to 10 with 1 mol / L sodium hydroxide aqueous solution. The mixture was stirred at 400-500 r / min for 2-4 h at 55-65℃, cooled naturally to room temperature, and stirred for another 12 h. The mixture was then centrifuged, washed three times with deionized water, and dried at 50-60℃ for 10-12 h under vacuum to obtain modified nanocellulose. (3) Polylactic acid, modified nano-titanium dioxide and modified nano-cellulose in a mass ratio of (18-20):1:1 are added to a melt spinning machine for melt spinning. After spinning, the fibers are immersed in deionized water for cooling and placed in a hot stretching box. The temperature is set at 60-80℃, the stretching ratio is 3.5 times, and the winding speed is 1000m / min to obtain polylactic acid fiber. (4) Polylactic acid fiber is subjected to plasma treatment using a low-temperature plasma treatment instrument. The vacuum is drawn to 35 Pa, the pressure reducing valve is opened, and ammonia is introduced to obtain ammoniated fiber. Phenylphosphonic acid, ethanol and deionized water are mixed evenly in a mass ratio of 1:(1~2):(19~20) to prepare a post-treatment solution. The ammoniated fiber is immersed in the post-treatment solution and reacted at 60~70℃ for 10~12h before being taken out to obtain plant-based antibacterial and deodorizing fiber.

8. The method for preparing a plant-based antibacterial and deodorizing fiber according to claim 7, characterized in that, The melt spinning parameters in step (3) are: melt temperature of 170-185℃ and spinneret diameter of 0.25-0.35mm.

9. The method for preparing a plant-based antibacterial and deodorizing fiber according to claim 7, characterized in that, The model of the low-temperature plasma processor is DT-03.

10. The method for preparing a plant-based antibacterial and deodorizing fiber according to claim 7, characterized in that, The parameters for the low-temperature plasma treatment in step (4) are: power (198-202) W, time (178-182) s.